Estrutura e relações ambientais de grupos florísticos em fragmento da floresta ombrófila mista, Rio Grande do Sul, Brasil - Greff, Luiz Thiago Brondani (2012)
This study was developed in a fragment of Mixed Ombrophylous Forest, located on National Forest of São Francisco de Paula in the state of Rio Grande do Sul, aiming to verify the formation of floristic groups and to characterize them in terms of structure, floristic composition and possible relations with the environment. Were allocated 16 plots of 50 by 50 m, totaling four hectares of sampling, where the vegetation with circumference at breast height. greater than 30 cm was measured. Soil characteristics and topographic variables were obtained to explore the environmental heterogeneity and possible relationship to the vegetation. The results were measured and identified 3171 trees distributed in 79 species, 55 genera, belonging to 32 botanical families. It was observed the formation of three floristic groups of which stands out the species Blepharocalyx salicifolius and Sebastiania commersoniana as characteristic species of a group that occurs in local small slope and soil relatively moist; Siphoneugena reitzii and Vernonanthura discolor as characterized an association with several exclusive species, small basal area and occur in places of great slopes and shallow soils, and also the species Araucaria angustifolia and Luehea divaricata characterize a third group, which occurs in areas of deep soil, good drainage, mean slope, and high basal area . It was observed through the logistic regression that changeable soil characteristics, topographical and structural of the vegetation affect in positive and negative way the occurrence probability them main species them florísticos groups.